(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The author’s major goal in this paper is to examine the idea of preventive detention under the Indian Constitution and to address the question of whether preventive detention can be considered a punishment for the purposes of criminology. The paper is split into three sections. The author briefly covers the various methods to Punishment, namely Punitive, Therapeutic, and Preventive, in the first half. The author investigates what constitutes punishment and what it entails. The opinions of many jurists, such as H.L.A. Hart, are used for this purpose. Preventive Detention is discussed in the next section as an insult to the all-pervasive idea of personal liberty. The Author delves into Article 22, substantiating it with major court rulings, as well as the history of Article 22 and the numerous preventive detention legislation now in force in India. The author also covers the Dimple Happy Dhakad case, which was a contentious ruling. In the final section, the author addresses the important topic of whether Preventive Detention is a Punishment. This section is supported by the author’s examination of several definitions of preventative detention and punishment. The author then discusses the declarations of several criminologists and asserts and shows a different viewpoint from them using modern Indian instances.